Measurement of pneumococcal capsular polysaccharide serotype-specific immunoglobulin G in human serum, a method for assigning weight-based units to proposed reference sera. - Rudolph, K M (1994)
A direct method for measuring serotype-specific, class-specific antibody in proposed human reference sera is described. The assay uses a 125I-labeled, isotopically pure immunoglobulin G (IgG) as a primary standard in an antigen-antibody solid-phase enzyme immunoassay. From the measurement of specific radioactivity bound to the absorbed antigen, serotype-specific IgG concentrations and optical density values can be directly related to optical density and serotype-specific IgG values for the reference serum. We used this method to provisionally assign IgG concentrations in a pneumococcal reference serum to serotypes 1, 3, 6A, 12F, 14 and 23F. This assay was found to be reproducible; the coefficient of variation for duplicates was within 5%, and the day-to-day coefficient of variation was from 3 to 18% for all six serotypes. The assay provides a general method for standardizing human reference serum tools with respect to concentration of antigen-specific IgM-, IgA-, and IgG-subclass antibodies.